2010
DOI: 10.1186/1471-2458-10-299
|View full text |Cite
|
Sign up to set email alerts
|

Reframing climate change as a public health issue: an exploratory study of public reactions

Abstract: BackgroundClimate change is taking a toll on human health, and some leaders in the public health community have urged their colleagues to give voice to its health implications. Previous research has shown that Americans are only dimly aware of the health implications of climate change, yet the literature on issue framing suggests that providing a novel frame - such as human health - may be potentially useful in enhancing public engagement. We conducted an exploratory study in the United States of people's reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
265
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(287 citation statements)
references
References 18 publications
12
265
1
9
Order By: Relevance
“…Our results are also consistent with past research that has found that a diversity of audience segments respond positively to an emphasis on the public health consequences of climate change and the health benefits of action (Maibach et al 2010). Furthermore, although emphasizing the national security implications of climate change has been assumed to be an effective strategy for engaging conservatives and other groups (Boykoff 2011), our findings show that in this instance (for reasons we speculate below) the national security frame actually generated substantial anger among the Doubtful and Dismissive segments of the public, both of whom lean conservative in their political outlook.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results are also consistent with past research that has found that a diversity of audience segments respond positively to an emphasis on the public health consequences of climate change and the health benefits of action (Maibach et al 2010). Furthermore, although emphasizing the national security implications of climate change has been assumed to be an effective strategy for engaging conservatives and other groups (Boykoff 2011), our findings show that in this instance (for reasons we speculate below) the national security frame actually generated substantial anger among the Doubtful and Dismissive segments of the public, both of whom lean conservative in their political outlook.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, it is increasingly being framed as a political problem. Social scientists, however, have suggested a variety of potential alternative frames, each of which can validly and accurately emphasize other relevant dimensions of the issue-such as public health, national security, extreme weather events, and/or the economy (Nisbet 2009;Nisbet and Scheufele 2009;Maibach et al 2010). Such alternative frames may be more effective at engaging audiences than the environmental or political frames that currently dominate public discourse.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As insuffi cient understanding of climate change is one of the largest perceived barriers to individual engagement, it is an important fi nding that the framing of climate change as a public health issue enhances engagement. [82][83][84] The Lancet Countdown will bring together evidence on changes in public understanding relating to health and climate change-more specifi cally, in terms of the perceived threats and opportunities of the responses. One possible long-term but resource-intensive approach would be to use phone-based and online public opinion polling techniques across a range of countries and settings.…”
Section: 1: Public Engagement With Health and Climate Changementioning
confidence: 99%